(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper, we have compared and analyzed the difference between quality of work life between government & private engineering institute faculties. The demographic profile affect on the quality work life of both the faculties government & private. Weighted average mean & standard mean helps to understand satisfaction level of employees.